Heat Stress Alters the Intestinal Microbiota and Metabolomic Profiles in Mice - Wen, Chaoyue; Li, Siyu; Wang, Jiaojiao; Zhu, Yimin; Zong, Xin; Wang, Yizhen; Jin, Mingliang (Frontiers in Microbiology, 2021)
Background: Heat stress has negative effects on the intestinal health of humans and animals. However, the impact of heat stress on intestinal microbial and metabolic changes remains elusive. Here, we investigated the cecal microbial and metabolic profiles in mice in response to heat stress. Methods: The mouse heat stress model was constructed by simulating a high-temperature environment. Twenty mice were randomly assigned to two groups, the control group (CON, 25°C) and the heat treatment group (HS, 40°C from 13:00 to 15:00 every day for seven days). Serum and cecal contents were collected from the mice for serum biochemical analysis, 16S rRNA high-throughput sequencing, and nontargeted metabolomics. Results: Both core body temperature and water intake were significantly increased in the HS group. Serum biochemical indicators were also affected, including significantly increased triglyceride and decreased low-density lipoprotein in the heat stress group. The composition and structure of intestinal microbiota was remarkably altered in the HS group. At the species level, the relative abundance of Candidatus Arthromitus sp. SFB-mouse-Japan and Lactobacillus murinus significantly reduced, while that of Lachnospiraceae bacterium 3-1 obviously increased after HS. Metabolomic analysis of the cecal contents clearly distinguished metabolite changes between the groups. The significantly different metabolites identified were mainly involved in fatty acid synthesis, purine metabolism, fatty acid metabolism, cyanoamino acid metabolism, glyceride metabolism, and plasmalogen synthesis. Conclusions: In summary, high temperature disrupted the homeostatic balance of the intestinal microbiota in mice and also induced significant alterations in intestinal metabolites. This study provides a basis for treating intestinal disorders caused by elevated temperature in humans and animals and can further formulate nutritional countermeasures to reduce heat stress-induced damage.